'No Coughing for Me, but I'm Okay!': A Human Service Worker's Narrative Exploration of Her Own and Other Workers' Body Stories Told in a Domestic Violence Service. (16th June 2017) - Mensinga, Jo
Abstract : Relational, body-oriented and brain-based approaches to recovery and change are increasingly popular modalities for working with traumatised children and adults. However, although these approaches encourage the awareness, and the harnessing of workers' visceral experiences, there is little in the literature to describe how practitioners navigate their own somatic maps. In a research project undertaken from 2008–16, I invited nine human service workers to tell and explore stories about their own experiences of the body that emerged during, and/or in relation to, their own professional practice. A narrative methodology was used to help facilitate a depth of understanding of how the participants used their own bodies as a source of knowledge and/or as an intervention strategy with those with whom they worked. In this paper, I explore one of many stories told by Coral in which she describes the processes she uses to navigate her own somatic map as she interacts with clients and workers in a domestic violence service. I conclude that creating spaces for workers to explore embodied experience in the professional conversation is important, but is difficult without an acceptable discourse or narrative template. Nonetheless, given the opportunity, including the 'body as subject' encourages better outcomes for clients and provides richer accounts of human service workers' professional experience.